Orthopädie - Theisen D; Malisoux L; Seil R; 2; Urhausen A; 2 (Deutsche Zeitschrift für Sportmedizin)
Organised youth sport has become increasingly professionalised, and the associated sports injury problem has received much attention lately. Sports injury prevention should rely on permanent surveillance and encompass the collection of epidemiological data, the establishment of risk factors, the implementation of prevention initiatives and the analysis of their effectiveness. Overall, injury incidence in youth sport is usually within a range of 1-10 injuries/1000 hours. About one fifth of all injuries are severe, implying a withdrawal from normal sport activity for at least 4 weeks, while up to 20% of all injuries are recurrences. Chronic overuse injuries amount to up to 40%, many of which concern episodes of traction apophysites, typical in youth sports. Risk factors can be extrinsic (e.g. sport context) or intrinsic (e.g. gender), modifiable (e.g. neuro-muscular control) or non-modifiable (e.g. previous injury). Injury risk is higher in team compared to individual sports and in competition compared to training. Active sports injury prevention initiatives have been introduced and tested in a number of controlled studies. Putting aside a possible publication bias, most results are encouraging, showing a possible reduction of injuries by 50% on average. Modern information technology can provide excellent solutions to assist in sports injury surveillance and prevention. One example of such an infrastructure is the Training and Injury Prevention Platform for Sports (www.tipps.lu) developed by the Sports Medicine Research Laboratory (CRP-Sant, Luxembourg).Key Words: sports injuries, injury incidence, injury mechanism, injury surveillance